Zagadnienie efektywności ochrony ubezpieczeniowej - Łańcucki, Jerzy (Wydział Prawa i Administracji UAM, 1973)
Effectiveness of insurance protection is widely discussed in professional publications in Poland and abroad, but the question has not been definitively settled yet. It seems that insurance indemnification may be treated as natural consequence resulting from the character of services rendered by an insurance company. In this situation effectiveness comes into prominence, but the effectiveness should be measured from the point of the insurant and not the Insurer, because it is the insurant who learns, in the hard way, of the effectiveness of insurance protection when there is an insurance case. Both the insurer and the insurant are interested in the accomplishment of insurance protection as the chief objective, but that unanimity becomes problematic when partial goals are to be achieved. Therefore effectiveness of insurance protection should be evaluated by the insurant; measurement of effectiveness done by the insurer is of no use. All attempts of that kind are only a formalized approximation to realities. It seems that effectiveness of insurance protection can be defined as relation between indemnification and the loss provided several conditions that depend upon the insurer and, first of all, upon the insurant have been fulfilled. An indispensable but insufficient condition is payment of damages by the insurer in the right amount and in due time. If these conditions are fulfilled, only potential effectiveness of insurance protection is secured and it is up to the insurant to make the protection real. Much depends on how and to what extent he will use the indemnification to repair the damage, which is dependent upon his initiative, enterprise and professional qualifications as well as on the availability of the necessary materials and products in the market and the amount of an additional subvention and loan.
The Problem of Effectiveness of Insurance Protection